1972
DOI: 10.1139/z72-189
|View full text |Cite
|
Sign up to set email alerts
|

Upper lethal temperatures of threespine stickleback, Gasterosteus aculeatus (L.), in relation to thermal and osmotic acclimation, ambient salinity, and size

Abstract: Samples of threespine sticklebacks, Gasterosteus aculeatus (L.), collected in seawater at Halifax, Nova Scotia, were acclimated to six combinations of conditions at 10 and 20C and in 0, 12, and 30‰ salinity (S). Bioassays of 10 000 min were performed at various constant temperatures from 20 to 30C in the diallel combinations of acclimation and salinities of 0, 12, and 30‰. Highest upper lethal temperatures, corresponding to combinations of acclimation, occurred in isosmotic test salinity of 12‰. Upper lethal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Every summer mortality of young of the year sticklebacks is recorded in shallow freshwater marshes and ditches, coinciding with water temperatures in excess of 25" C. The saline lagoons, being larger and deeper, are not subject to such high temperatures as the shallow freshwater bodies. Trachurus type Gasterosteus aculeatus are reported to have a higher upper lethal temperature in brackish water than in either fresh or sea water (Jordan & Garside 1972) but it is not known whether this is also true for leiurus fish. During the hottest months (July to September) surviving sticklebacks show reduced growth rates, which are probably at least in part attributable to unfavourably high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Every summer mortality of young of the year sticklebacks is recorded in shallow freshwater marshes and ditches, coinciding with water temperatures in excess of 25" C. The saline lagoons, being larger and deeper, are not subject to such high temperatures as the shallow freshwater bodies. Trachurus type Gasterosteus aculeatus are reported to have a higher upper lethal temperature in brackish water than in either fresh or sea water (Jordan & Garside 1972) but it is not known whether this is also true for leiurus fish. During the hottest months (July to September) surviving sticklebacks show reduced growth rates, which are probably at least in part attributable to unfavourably high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The number of hours that water temperature was above 25°C and dissolved oxygen was below 2 ppm was included in our multiple regression analysis, since these conditions represent potentially stressful conditions for the fish. For example, Jordon and Garside (1972) observed that the upper lethal temperatures for threespine sticklebacks were between 21.63 and 28.76"C and averaged 26.2"C. The physicochemical conditions in the tide pools for the periods between clutches and for the total time females remained in the pools are presented in Tables 2 and 3, respectively. No data are available for May 1986, since none of the females completed two reproductive cycles (Table 2).…”
Section: Fecundity (Tide Pool Fish)mentioning
confidence: 99%
“…These fish occur in shallow freshwater and marine habitats with a temperature range from 4 to 20°C [[31]], but show preferences for intermediate temperatures (15-18°C [[32],[33]]). Our experimental temperature environments were set to simulate the average summer temperature of coastal North Sea areas (i.e.…”
Section: Introductionmentioning
confidence: 99%